A global perspective on improving patient care in uncomplicated urinary tract infection: expert consensus and practical guidance. (March 2022) - Wagenlehner, Florian; Nicolle, Lindsay; Bartoletti, Riccardo; Gales, Ana C.; Grigoryan, Larissa; Huang, Haihui; Hooton, Thomas; Lopardo, Gustavo; Naber, Kurt; Poojary, Aruna; Stapleton, Ann; Talan, David A.; et al.
Highlights: Diagnosis of uncomplicated urinary tract infection (uUTI) is typically symptom-based. uUTI is treated empirically with antibiotics. Antimicrobial resistance (AMR) is a growing concern with antibiotics used to treat uUTIs. Risk factors for AMR can be identified without urine culture. Abstract: Objectives: Uncomplicated urinary tract infections (uUTIs) are a common problem in female patients. Management is mainly based on empirical prescribing, but there are concerns about overtreatment and antimicrobial resistance (AMR), especially in patients with recurrent uUTIs. Methods: A multidisciplinary panel of experts met to discuss diagnosis, treatment, prevention, guidelines, AMR, clinical trial design and the impact of COVID-19 on clinical practice. Results: Symptoms remain the cornerstone of uUTI diagnosis, and urine culture is necessary only when empirical treatment fails or rapid recurrence of symptoms or AMR is suspected. Specific antimicrobials are first-line therapy (typically nitrofurantoin, fosfomycin, trimethoprim/sulfamethoxazole and pivmecillinam, dependent on availability and local resistance data). Fluoroquinolones are not first-line options for uUTIs primarily due to safety concerns but also rising resistance rates. High-quality data to support most non-antimicrobial approaches are lacking. Local AMR data specific to community-acquired uUTIs are needed, but representative information is difficult to obtain; instead, identification of risk factors for AMR can provide a basis to guide empirical antimicrobial prescribing. The COVID-19 pandemic has impacted the management of uUTIs in some countries and may have long-lasting implications for future models of care. Conclusion: Management of uUTIs in female patients can be improved without increasing complexity, including simplified diagnosis and empirical antimicrobial prescribing based on patient characteristics, including a review of recent antimicrobial use and past pathogen resistance profiles, drug availability and guidelines. Current data for non-antimicrobial approaches are limited. The influence of COVID-19 on telehealth could provide an opportunity to enhance patient care in the long term.